Identification of Phyciodes diminutor, P. cocyta, and P. tharos in northeastern U.S. (Nymphalidae) - Scott, James A., author; James A. Scott, publisher (Colorado State University. Libraries, 2014)
This issue of Papilio (New Series) consists of three studies on the identification of the closely-related species Phyciodes diminutor diminutor Scott, P. cocyta selenis (W. Kirby)and P. tharos tharos (Drury), from Vermont, Ohio, and Michigan (studies labeled A, B, and C below). Identification problems have hindered the study of these butterflies in the northeastern U.S., and misidentifications have even occurred in recent DNA studies. Difficulties in distinguishing diminutor & selenis, and their status, are discussed. Vermont contains all three taxa in this group. P. tharos has two generations and occurs in southern and central Vermont, north to Woodsville on the Connecticut River on the E edge of Vermont, and occurs also on North and South Hero Islands in Lake Champlain in extreme NW Vermont. P. cocyta has one generation and evidently occurs in the cooler areas throughout Vermont except in the two southern counties Bennington and Windham. P. diminutor has two generations and evidently occurs throughout Vermont if it belongs to a separate species P. diminutor as studies elsewhere suggest. Michigan has all three species, while northern Ohio (including Lucas Co.) has P. tharos and P. diminutor. Few of the specimens of P. cocyta, P. tharos, and P. batesii used in the mtDNA study of Proshek & Houghton (2006) were misidentified (among all specimens examined, a few "tharos" and "cocyta" are P. diminutor, some "batesii" females from one site are P. cocyta, and all "cocyta" from S Mich. are P. diminutor). mtDNA is not usable to identify any of these species. The proper future research plan is described, which includes rearing numerous families found on wild identified hostplants from localities with multiple taxa.
Keywords: Butterflies; Lepidoptera